Minimally invasive surgery as a new clinical standard for bone anchored hearing implants—real-world data from 10 years of follow-up and 228 surgeries - Cruz, Leonardo Di Santana; Danieli, Fabiana; Håkansson, Maria Åberg; Johansson, Martin Lars; dos Santos, Francine Raquel; Mirândola Barbosa Reis, Ana Claudia; Hyppolito, Miguel Angelo (Frontiers in Surgery, 2023)
Purpose To explore the clinical practice development of different surgical techniques when installing bone-anchored hearing implants and their associated trends in outcomes. Design Retrospective study of 228 bone-anchored hearing implants in 200 patients, performed over a 10-year period between 2012 and 2022 in a referral hospital. Method Real-world data of demography, etiology, surgical setup, complications, and audiological outcomes were collected. Eligibility criteria from clinical practice were applied. Results The minimally invasive technique is associated with shorter surgery duration, 20 vs. 44 min as compared to a linear incision technique. The minimally invasive technique was also associated with a lower occurrence of complications when compared to linear incision techniques (intraoperative; 1.8% vs. 4.9%, postoperative; 49% vs. 66%). Most differences were seen in complications relating to skin and wound healing. Conclusion Adoption of a minimally invasive surgical technique for the installations of bone-anchored hearing implants can reduce surgical complexity without compromising safety aspects or clinical benefits.